ANALISIS DAYA SAING KOMODITI LADA DI KABUPATEN KOLAKA TIMUR - Nursalam Nursalam; Yuli Purbaningsih; Muh Obi Kasmin (JURNAL AGRIBISNIS TERPADU, 2018)
Pepper farm is the one of leading sector in East Kolaka Regency who can be a main contributor in Gross Domestic Regional Product (GDRP) structure along with cocoa farm.  Pepper farm has become a economic source for most of the people in the area.  This study aimed to analysis the competitiveness of pepper commodities at the farm level in East Kolaka Regency.  This study used the policy Analysis Matrix (PAM) to analyze the data.  The results of the study showed pepper commodity in East Kolaka Regency has a high level of competitiveness as shown by the DRCR value of 0,62 and PCR value of 0,71.  The government`s policy of input-output showed that there is a government policy which reduce the benefits of cocoa producer in East Kolaka Regency as indicated by the PC value of 0,8316.  The value of PC also showed how many a potential profitability that can be accepted by a farmers, that is equal to 16,84%.